Macrolinguistics: A Pragmatics Study of Speech Act In ‘Just Cute Conversation with Stranger On Ometv - Sugiarto, Sindy Oktaviani; Susylowati, Eka (Jurnal Ilmu Sosial dan Humaniora, 2025)
The essential point is to analyze how casual intelligent unfurl and to distinguish particular designs affected by social and social settings. Whereas past inquire about has frequently cantered on points such as online security or computerized morals, this think about highlights the practical perspectives of casual communication. Through talk investigation of collected discussion tests, the investigate uncovers that discourse acts in these amusing trades tend to be looser and more unconstrained compared to formal intuitive. Key designs incorporate humour, wit, and passionate expression, which altogether improve social mindfulness and interpersonal associations. The discoveries give important experiences into the workings of pragmatics in online social intelligent, especially within the setting of carefree trades on Ometv. This inquiries about contributes to a more profound understanding of how advanced innovation shapes human behaviour in different social circumstances.